In silico analysis of SARS-CoV-2 spike protein N501Y and N501T mutation effects on human ACE2 binding - Cubuk, Hasan; Ozbil, Mehmet (Elsevier Science Inc, 2022)
The SARS-CoV-2 is an RNA-based virus and the most vital step of its survival is the attachment to hACE2 through its spike protein. Although SARS-CoV-2 has the ability to maintain high accurate replication and it can be accepted as a low mutation risked virus, it already showed more than nine thousand mutations in spike protein, of which 44 mutations are located within a 3.2 angstrom interacting distance from the hACE2 receptor. Mutations on spike protein, N501Y and N501T raised serious concerns for higher transmissibility and resistance towards current vaccines. In the current study, the mutational outcomes of N501Y and N501T on the hACE2-SARS CoV-2 spike protein complexation were analyzed by employing all-atom classic molecular dynamics (MD) simulations. These simulations revealed that both N501Y and N501T mutations increased the binding strength of spike protein to the host hACE2, predicted by binding free energy analysis via MM/GBSA rescoring scheme. This study highlights the importance of energy-based analysis for identifying mutational outcomes and will shed light on handling long-term and effective treatment strategies including repurposing anti-viral drugs, anti-SARS-CoV-2 antibodies, vaccines, and antisense based-therapies.
Keywords: SARS-CoV-2 mutations; N501Y and N501T mutations; hACE2-SARS-CoV-2 spike protein binding; Effect of mutations on binding energy; Molecular Dynamics simulations